Sustained-release losartan from peptide nanofibers promotes chondrogenesis - Yamaura, Kohei; Sather, Nicholas A.; Metlushko, Anna; Nishimura, Haruki; Pavlović, Radoslav Z.; Hambright, Sealy; Ravuri, Sudheer K.; Philippon, Marc J.; Stupp, Samuel I.; Bahney, Chelsea S.; Huard, Johnny (Frontiers in Bioengineering and Biotechnology, 2023)
The central pathologic feature of osteoarthritis (OA) is the progressive loss of articular cartilage, which has a limited regenerative capacity. The TGF-β1 inhibitor, losartan, can improve cartilage repair by promoting hyaline rather that fibrous cartilage tissue regeneration. However, there are concerns about side effects associated with oral administration and short retention within the joint following intra-articular injections. To facilitate local and sustained intra-articular losartan delivery we have designed an injectable peptide amphiphile (PA) nanofiber that binds losartan. The aims of this study are to characterize the release kinetics of losartan from two different PA nanofiber compositions followed by testing pro-regenerative bioactivity on chondrocytes. First, we tested the impact of electrostatic interactions on nanostructure morphology and release kinetics of the negatively charged losartan molecule from either a positively or negatively charged PA nanofiber. Subsequently, cytotoxicity and bioactivity were evaluated in vitro using both normal chondrocytes and an IL-1β-induced OA chondrocyte model. The results of this study showed that both nanofiber systems promote cell proliferation but that the positively-charged nanofibers also significantly increase glycosaminoglycans production. Furthermore, gene expression analysis suggested that losartan-encapsulated nanofibers had significant anti-inflammatory, anti-degenerative, and cartilage regenerative effects by significantly blocking TGF-β1 in this in vitro system. The results demonstrated that positively charged losartan sustained-release nanofibers may be a novel and useful treatment for cartilage regeneration and OA by blocking TGF-β1.